Determinants of Continuity in Conventional Industrial Channel Dyads - Anderson, Erin; Weitz, Barton (Marketing Science, 1989)
Recently, increasing attention has been paid to the question of how to build stable, long-term relationships between manufacturers and members of conventional channels. This descriptive field study concerns a basic requirement for building long-term relationships, which is the expectation by a marketing intermediary that the relationship will last. Hypotheses about the continuity of relationships are developed from the literature on social exchange, bargaining, and negotiation. These hypotheses are framed as a simultaneous equation system, which is estimated via three-stage least squares on a sample of 690 relationships (dyads) involving manufacturers and their independent sales agents (manufacturers' representatives). Results substantially support the model, highlighting the importance of interpersonal relationships in insuring the continuity of the dyad.